Motivational Strategies in EFL Classes in Indonesia - Rizki Februansyah; Muhammad Ahsanu; Audi Yundayani (Journey: Journal of English Language and Pedagogy, 2023)
The current study is aimed at revealing the motivational strategies employed by EFL lecturers in two universities in Purwokerto, Central Java. This research falls into the qualitative category since it attempts to examine the data in the form of testimonies on how they motivated their students in their EFL classes. There were five EFL lecturers involved in this study and to collect the data, the researcher conducted semi-structured interview either offline or online. The collected data were then analyzed using thematic analysis. The results of the study show that the EFL lecturers employed four strategies namely using music, employing verbal motivation, building rapport with students, and hiring collaborative learning. Theoretically, the research can harness the knowledge on the motivational strategies in the Higher Education Institutions context especially in the Teaching of English as a Foreign Language. Practically, the results of the research may become alternative sources for teachers’ self-development